2011
DOI: 10.1193/1.3636386
|View full text |Cite
|
Sign up to set email alerts
|

Haiti Building Failures and a Replicable Building Design for Improved Earthquake Safety

Abstract: Christianville is a group of U.S. mission projects (education, medical, dental, and eye) located 8 km east of Léogâne and near the epicenter of the 12 January 2010 earthquake. The facility consists of a conglomeration of buildings built using Haitian construction methods over the past 40 years and serves as a microcosm of Haitian building techniques in the remainder of the country. There was significant variation in the performance of the buildings during the earthquake—some buildings completely collapsed, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Post-earthquake reconnaissance reports [10], [11] from previous earthquakes around the world have detailed the poor performance of buildings with lightly reinforced concrete columns. Investigations of these buildings showed that the predominant cause of collapse was axial failure of gravity loading carrying components.…”
Section: Behavior Of Existing Non-ductile Columnsmentioning
confidence: 99%
“…Post-earthquake reconnaissance reports [10], [11] from previous earthquakes around the world have detailed the poor performance of buildings with lightly reinforced concrete columns. Investigations of these buildings showed that the predominant cause of collapse was axial failure of gravity loading carrying components.…”
Section: Behavior Of Existing Non-ductile Columnsmentioning
confidence: 99%
“…It is important to note that these hazard data were calculated assuming a firm rock site, implying that the PGA could be higher for soil sites due to their amplification potential, as shown by Ulysse et al [6][7][8] and St-Fleur et al [9]. In addition to hazard understanding, the vulnerability of buildings is as a crucial component in seismic risk assessment, with numerous earthquake reconnaissance studies post the 2010 and 2021 earthquakes enriching the literature on this aspect [1,2,[11][12][13][14][15][16][17][18]. Typically, the high vulnerability of structures is attributed to factors such as low-quality materials, insufficient reinforcement in reinforced concrete members, non-ductile design, and the fact that buildings were mostly designed for gravity loads but not for seismic and horizontal loads.…”
Section: Introductionmentioning
confidence: 99%
“…Scawthon [14] reported the damage in all building typologies after the 2004 Niigata earthquake in Japan and concluded that newer constructions performed better than other building types. Holliday and Grant [15] presented an account of collapsed and survived buildings during the 2010 Haiti earthquake. Similar case studies were also presented by Gautam and Rodrigues [16] for the buildings affected by several earthquakes in Nepal.…”
Section: Introductionmentioning
confidence: 99%